Bioactive compounds of two orange-fleshed sweet potato cultivars (Ipomoea batatas (L.) Lam.) in fresh, stored and processed roots - Gabilondo, Julieta (2022)
Sweet potatoes are a rich source of bioactive compounds, which are considered to promote human health. This study aimed to analyse the main bioactives of two orange-fleshed sweet potato cultivars, Beauregard and Colorado INTA, freshly harvested, after storage, and after processing of sweet potato paste, a solid dessert widely consumed in Argentina. In the flesh, phenolic compounds, carotenoids, anthocyanin contents, and radical scavenging activity were significantly higher in Colorado INTA cultivar. The carotenoid contents were 555 and 712 µg β-carotene/g dw in the flesh of Beauregard and Colorado INTA, respectively. In the peel of both cultivars, phenolic contents and antioxidant activities were notably higher than in the flesh. Extended storage has markedly increased phenolics and antioxidant properties in the flesh of Colorado INTA, further accentuating the differences between both cultivars. Paste processing negatively affected all parameters, particularly in Beauregard. The major phenolic compounds in both cultivars, chlorogenic and 3,5-dicaffeoylquinic acids, were the most affected by processing. The main reductions of bioactives stemmed from sugar addition. The inclusion of the peel, traditionally discarded during processing, could confer an additional value to the paste. The high bioactive contents of Beauregard and Colorado INTA cultivars, especially the latter, can contribute to provide health benefits and to reduce vitamin A deficiency. The valuable attributes of these cultivars could represent a useful tool for sweet potato producers to add value to this product and to foment its consumption.